2017
DOI: 10.1002/smll.201700962
|View full text |Cite
|
Sign up to set email alerts
|

Writing with Fluid: Structuring Hydrogels with Micrometer Precision by AFM in Combination with Nanofluidics

Abstract: Hydrogels have many applications in biomedical surface modification and tissue engineering. However, the structuring of hydrogels after their formation represents still a major challenge, in particular due to their softness. Here, a novel approach is presented that is based on the combination of atomic force microscopy (AFM) and nanofluidics, also referred to as FluidFM technology. Its applicability is demonstrated for supramolecular hydrogel films that are prepared from low-molecular weight hydrogelators, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Therefore, the incorporation process did not lead to alteration of the NLC structure, size, or morphology, and there was no effect on particle aggregation, showing that the NLCs remained stable after incorporation in the hydrogel. There have been various reports of AFM used to analyze the topography of hydrogels (Helfricht et al, 2017). El-Mekawy and Jassas (2017) described the synthesis of insulin systems employing ZnO nanoparticles in chitosan hydrogel, with analyses using AFM, transmission electron microscopy (TEM), and scanning electron microscopy (SEM), showing that the film exhibited porosity and that nanoparticles were present in the matrix, corroborating the present findings.…”
Section: Morphologies Of the Nanostructured Lipid Carriers In Suspension And Gelsupporting
confidence: 84%
“…Therefore, the incorporation process did not lead to alteration of the NLC structure, size, or morphology, and there was no effect on particle aggregation, showing that the NLCs remained stable after incorporation in the hydrogel. There have been various reports of AFM used to analyze the topography of hydrogels (Helfricht et al, 2017). El-Mekawy and Jassas (2017) described the synthesis of insulin systems employing ZnO nanoparticles in chitosan hydrogel, with analyses using AFM, transmission electron microscopy (TEM), and scanning electron microscopy (SEM), showing that the film exhibited porosity and that nanoparticles were present in the matrix, corroborating the present findings.…”
Section: Morphologies Of the Nanostructured Lipid Carriers In Suspension And Gelsupporting
confidence: 84%
“…In this work, we replaced the cinnamate with benzoic acid (BTABA), which has been widely reported in supramolecular gel systems. As shown in Figure b, we found that the VAA method is still effective in the BTABA system, and the chiral bias is drastically boosted ( g lum = ±4.35 × 10 –2 ). More importantly, the resultant assemblies can be used as chiral seeds and further control the handedness of CPL in the following VAA treatment.…”
Section: Introductionmentioning
confidence: 93%
“…Analogous to previous benzene-1,3,5-tricarboxamide (BTA) derivatives, BTABA can form helical nanoribbons in a mixture of good solvent (DMF) and poor solvent (H 2 O) with the volume ratio of 6:4. However, the sample has no optical activity due to the equal number of left- and right-handed helixes.…”
Section: Resultsmentioning
confidence: 99%